The Influence of Organizational Communication and Employee Integrity on the Service Quality of Junior High School Teachers in Tungkal Ilir Subdistrict in Enhancing the Public Image of the Department of Education and Culture of Tanjung Jabung Barat Regency - Najri, Pauzan; Suryani, Arna; Sudirman, Sudirman (Dinasti International Journal of Management Science, 2025)
This study has several objectives, including: 1) To describe organizational communication, integrity, service quality and image of public institutions at the Department of Education and Culture of West Tanjung Jabung Regency; 2) To analyze the influence of organizational communication on service quality; 3) To analyze the influence of integrity on service quality; 4) To analyze the influence of organizational communication on the image of public institutions; 5) To analyze the influence of integrity on the image of public institutions; 6) To analyze the influence of service quality on the image of public institutions; 7) To analyze the influence of organizational communication through service quality on the image of public institutions; and 8) To analyze the influence of integrity through service quality on the image of public institutions. This research was conducted at the Education and Culture Office of West Tanjung Jabung Regency. The population was 125 teachers at SMPN Tungkal Ilir District, West Tanjung Jabung Regency. The sample size used Slovin's theory with a 5% margin of error, resulting in 96 teachers. This research employed a quantitative approach with a survey method and Partial Least Square (PLS) data analysis. The results of the study indicate that organizational communication and integrity have an influence on the image of public institutions, both directly and indirectly through the quality of service at the Education and Culture Office of West Tanjung Jabung Regency. This indicates that the Education and Culture Office of West Tanjung Jabung Regency is able to build effective internal communication and uphold the integrity of its employees will more easily form a positive image in the eyes of the public. Thus, the image of a public institution is not only determined by its external appearance, but also by how the institution communicates and upholds the values of honesty in providing services to the public.